1991
DOI: 10.1111/j.1365-2818.1991.tb03073.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature scanning electron microscopy in biology

Abstract: SUMMARY A review of low‐temperature scanning electron microscopy (LTSEM) with regard to preparation protocols, specimen preservation, experimental approaches, and high‐resolution studies, is provided. Preparative procedures are described and recent developments in methodologies highlighted. It is now well established that LTSEM, for most biological specimens, provides superior specimen preservation than does ambient‐temperature SEM. This is because frozen‐hydrated samples retain most or all of their water, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…A review of the literature revealed that fusion between spore germlings is common, and over 20 species were found to produce structures similar to CATs (35,36). Köhler (24) first showed fusion between germlings of Neurospora spp.The initial aim of the present study was to analyze the morphogenetic process of fusion between conidia and conidial germlings of N. crassa by using confocal live-cell imaging (9, 16) and low-temperature scanning electron microscopy of frozen-hydrated samples (33,34). We found that the three types of conidia (macroconidia, microconidia, and arthroconidia) produced by N. crassa (40) form CATs that are morphologically distinct and different in behavior from germ tubes.…”
mentioning
confidence: 99%
“…A review of the literature revealed that fusion between spore germlings is common, and over 20 species were found to produce structures similar to CATs (35,36). Köhler (24) first showed fusion between germlings of Neurospora spp.The initial aim of the present study was to analyze the morphogenetic process of fusion between conidia and conidial germlings of N. crassa by using confocal live-cell imaging (9, 16) and low-temperature scanning electron microscopy of frozen-hydrated samples (33,34). We found that the three types of conidia (macroconidia, microconidia, and arthroconidia) produced by N. crassa (40) form CATs that are morphologically distinct and different in behavior from germ tubes.…”
mentioning
confidence: 99%
“…Glomus intraradices, T. harzianum and R. solani) on autotrophic potato plantlets as a single host. For the three fungi, the hyphal extension, colonization of the substrate, root infection/colonization and reproduction structures were described under autotrophic in vitro culture conditions (Voets et al, 2005), combining the video camera imaging (De la Providencia et al, 2005) and the cryo-electron scanning microscope (cryo-SEM) (Read and Jeffree, 1991).…”
mentioning
confidence: 99%
“…Thus, images with good representation of three-dimensional shape of samples can be achieved [Wikipedia]. SEMs equipped with cold stage for cryo-microscopy can be used for cryofixation as low temperature SEM [Read & Jeffree, 1991]. Cryo-fixed specimens can also be cryo-fractured under vacuum to reveal internal structures [Faulkner et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Glutaraldehyde and osmium tetroxide are often used to crosslink protein molecules and to preserve lipids, respectively. This step is followed by post-fixation with osmium tetroxide (OsO4) [Read & Jeffree, 1991]. A buffer containing sodium cacodylate, Sucrose and 2-Mercaptoethanol is recommended if precipitation is visible in final sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation